Religiosity in Post-Secular Society - Malika Medkour (أنساق, 2021)
This article discusses the theme of the new wave of return to religion in the public sphere, and the growing calls in post-secular societies to return to moral values and religion and to their seek assistance in solving scientific and social problems alike. This comes after postmodernism revealed the evil of Western modernity and the collapse of its principles and ideas, including the principles that contributed to building the foundations and principles of social and human sciences.